2014
DOI: 10.1371/journal.pone.0106262
|View full text |Cite|
|
Sign up to set email alerts
|

Apelin Receptor (APJ) Expression during Cardiopulmonary Bypass in Children Undergoing Surgical Repair

Abstract: Background and AimsIn human adults, and animals, the Apelin-APJ ligand-receptor system is emerging as having a role in the pathogenesis of cardiovascular function and heart failure. The aim was to investigate expression, and regulation by oxygen, of the Apelin APJ receptor (APJ) in myocardium obtained from children undergoing corrective surgery with cardiopulmonary bypass for repair of congenital heart defects.MethodsWestern blotting and Real-time PCR were used to determine if APJ was expressed in the infant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…Apelin orthologues are present in many species including pig, rhesus macaque, cow and zebrafish. Apelin and apelin receptor have been shown previously to be expressed in cardiomyocytes of human ( Kleinz et al., 2005 , Walker et al., 2014 ) and rodents ( Ronkainen et al., 2007 , Kawamata et al., 2001 ). Apelin is synthesised as pre-proapelin, a 77 amino acid pre-proprotein ( Tatemoto et al., 2001 ).…”
Section: Introductionmentioning
confidence: 94%
“…Apelin orthologues are present in many species including pig, rhesus macaque, cow and zebrafish. Apelin and apelin receptor have been shown previously to be expressed in cardiomyocytes of human ( Kleinz et al., 2005 , Walker et al., 2014 ) and rodents ( Ronkainen et al., 2007 , Kawamata et al., 2001 ). Apelin is synthesised as pre-proapelin, a 77 amino acid pre-proprotein ( Tatemoto et al., 2001 ).…”
Section: Introductionmentioning
confidence: 94%
“…The endogenous agonist of the apelin receptor apela mRNA was detected in the rat heart [ 18 ]. It was demonstrated that the apelin receptor is expressed in the atrial tissue and heart ventricles of rats [ 25 ] and in the human heart [ 26 ]. The apelin receptor was identified in the epicardial coronary arteries of rats [ 27 ].…”
Section: Cardiovascular Effects Of Apelinsmentioning
confidence: 99%
“…na aktywacji receptora naskórkowego czynnika wzrostu i fosfatazy [48,51,52]. Zmiany w ekspresji receptora APJ w układzie sercowo-naczyniowym badano także u dzieci poddanych operacjom kardiochirurgicznym z powodu wad serca, jednak wyniki nie były jednoznaczne [53].…”
Section: Aktywność Biologiczna I Angiogenezaunclassified